PENGARUH KINERJA KERELASIAN PELANGGAN DAN SISTEM PENYAMPAIAN JASA TERHADAP NILAI PELANGGAN SERTA DAMPAKNYA PADA KEPERCAYAAN PELANGGAN DAN REPUTASI PERUSAHAAN (Survey pada Pelanggan Telepon Seluler di Bandung) - Bambang Fajarisman (Indonesian Journal of Economics and Business, 2011)
This survey investigated  the influence of performance  of customer relationship and service delivery system on customer value and it’s impacts on customer trust and corporate reputation. The most aspect of life will be changed quickly and unpredictible. The modern people in the world  need supporting facilities for mobility communication and information access. According to that situation and condition, celluer indstry is the important infrastucture for facilitation  the  dinamic people need. The high competition in celluler industry give negative impact to operators e.g churn customer. In case, all operators give the product and service through developing the customer relationship for along time with the excellent delivery service system, so that will be produced superior value customer and strong customer trust and than finally, the best corporate reputation.The respondens  is consist of celluler customers in Bandung.The result is dianalyzed by frequently distribution analyzed  for describing  the performance of customer relationship and service delivery system, and  than by structural equation modelling for measuring the influence of customer relationship and service delivery system to corporate reputation through customer value anda customer trust.Finally, the customer ralationship influence corporate reputation significanly, but service delivery system did’nt give a better result.